Orthographic Cues to Stress Affect Reading in Connected Text: Evidence From a Letter-Detection Task. - Sparks, Erin; Deacon, S. Hélène (Canadian Journal of Behavioural Science, 2024)
In English, written word endings act as probabilistic cues to a word's lexical stress pattern. Readers are sensitive to these statistical associations between lexical stress and spelling, using word endings' spellings to guide stress placement when reading isolated words. However, we do not yet know if readers' use of endings as stress cues extends to the processing of words in connected text. In the present study, we explored this question with adult readers (N = 53). Participants read texts for comprehension while circling a specified target letter. This letterdetection task can speak to the processes involved in reading words, as readers detect fewer letters when lexical access is relatively quick. Adults detected fewer target letters in words whose endings accurately cued their stress patterns than in words whose endings gave misleading cues to stress (d = 0.41). This suggests that adult readers draw on written word endings as cues to stress during the everyday task of reading for comprehension. These findings clarify the scope of word endings' role as cues to stress in English.